The role of plyometrics in the scope of a periodized training model - Pettitt, R. (The Journal of Performance Enhancement, 1999)
The role of plyometrics in the scope of a periodized training model. J. Perf. Enhan. 1999 1(1):11-20. Plyometric drills are often periodized across an athlete`s competitive year according to their levels of difficulty or intensity. The periodized model assists the performance enhancement professional in structuring a program that prevents injury and overtraining and enables athletes to peak in muscular performance at a more critical point in the competitive season. A reduction of the amortization phase, greater cross sectional recruitment, and a threshold elevation for the inverse stretch reflex are among the physiological adaptations that occur from plyometric training. Several criteria are used in evaluating the intensity level of a plyometric session. These criteria help in determining the appropriateness of plyometrics throughout a competitive year and should be considered in conjunction with the athlete`s previous training history.